Development of Munzur trout (Salmo munzuricus) and determination of antioxidant enzyme activities in recirculating aquaculture system - Can, Erkan; Özçiçek, Esin; Benzer, Fulya; Erişir, Mine; Kızak, Volkan; Kocabaş, Prof. Dr. Mehmet; Yılmaz, Kadir (Kastamonu Üniversitesi, 2022)
In the study, a recirculating aquaculture system (RAS) was established, which is becoming widespread as much as it is in the production of marine fish in trout production today. The development and antioxidant enzyme activities of the juvenile fish hatched from the eggs taken from the broodstocks obtained from Munzur Stream were investigated. The trout fries (0.5±0.13 g) were stocked in 8 fiberglass tanks in the recirculating aquaculture system established within the scope of the project and fed for 120 days. The development parameters were recorded on a monthly basis. Then, at the 90th and 120th days, tissue samples were taken from the gill, liver and muscles to determine the oxidant and antioxidant balance, glutathione (GSH) and malondialdehyde (MDA) levels, superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase. (CAT) activities were analyzed. At the end of the study, the MDA concentration and GSH level were found to be highest in the gills. It was determined that there were differences between GSH-Px and CAT activities in muscle tissues (p<0.05). SOD activity showed a significant increase in muscle compared to other organs. The data obtained as a result of the study is also a source for studies to be carried out on the conservation of Munzur trout, whose numbers are decreasing day by day, within the scope of biodiversity, and for commercial studies.

Çalışmada, günümüzde alabalık üretiminde de deniz balıkları üretiminde olduğu kadar kullanımı hızla yaygınlaşan kapalı devre akuakültür sistemi kurulmuştur. Munzur Çayı’ndan temin edilen anaçlardan alınan yumurtalardan çıkan yavru balıkların gelişimi ve antioksidan enzim aktiviteleri araştırılmıştır. Munzur alabalığı yavruları (0,5±0,13 g) proje kapsamında kurulan kapalı devre yetiştiricilik sistemindeki 8 adet fiberglas tankta stoklanmış ve 120 gün boyunca beslenmiştir. Aylık olarak gelişim parametreleri kaydedilmiştir. Daha sonra 90. ve 120. günlerde de oksidan ve antioksidan dengesinin belirlenmesi için solungaç, karaciğer ve kaslardan doku örnekleri alınarak redükte glutatyon (GSH) ve malondialdehyde (MDA) düzeyleri ile süperoksit dismütaz (SOD), glutatyon peroksidaz (GSH-Px) ve katalaz (KAT) aktiviteleri analiz edilmiştir. Çalışmanın sonunda, MDA konsantrasyonu ve GSH düzeyi solungaçlarda en yüksek bulunmuştur. Kas dokularında GSH-Px ve KAT aktivitesinde gruplar arasında farklılıkların olduğu belirlenmiştir (p<0,05). SOD aktivitesi, kaslarda diğer organlara kıyasla önemli bir artış gözlenmiştir. Çalışma sonucunda elde edilen veriler, sayıları gün geçtikçe azalmakta olan Munzur alabalığının biyo-çeşitlilik kapsamında korunması üzerine yapılacak olan çalışmalar ile ticari olarak yapılacak çalışmalar için de kaynak niteliğindedir.
Munzur alabalığı (Salmo munzuricus)’nın kapalı devre yetiştiricilik sisteminde gelişimi ve antioksidan enzim aktivitelerinin belirlenmesi
Keywords: Hydrobiology; Hidrobiyoloji